CULTURAL SPECIFIC ATTITUDES OF BATSWANA PEOPLE TOWARDS ADOPTION - Ratshidi, Katlego; Boshoff, Pieter (Social Work/Maatskaplike Werk, 2019)
The aim of this study was to describe the cultural attitude of Batswana people towards adoption. The study employed a cross-sectional survey design and is descriptive in nature. It followed a quantitative approach and reached 83 respondents representative of designated organisations rendering services to adoptive parents in Ikageng, Potchefstroom. A questionnaire containing closed-ended questions was used. Demographical information was included to test the construct validity on different variables, namely the birthparent, adoptive parent and the adopted child. The findings of the study indicated that the Batswana community have a positive attitude towards adoption